Implementasi Teori Kognitif Dan Spiritualitas Dalam Sekolah Tinggi Teologi: Implementation of Cognitive Theory and Spirituality in Theological College - Sofiah Lentjang; Dunant F. Soukotta; Tan Winda (MODERATE: Journal of Religious, Education, and Social, 2023)
Education in Theological Colleges often emphasizes cognitive theory while neglecting spirituality, leading to students who are intellectually capable but spiritually dry. This study aims to highlight the importance of integrating cognitive theory and Christian spirituality in theological education so that students not only master knowledge but also embody Christ-like character. The research uses a qualitative literature review method, analyzing books, journals, and biblical texts related to cognitive learning theory and spiritual formation. The results show that without strong spirituality rooted in God’s Word and the example of Jesus Christ, high cognitive ability can lead to arrogance, moral failure, and an inability to be a living testimony. Therefore, theological colleges must prioritize spiritual formation—including humility, love, self-control, prayer, and obedience—alongside cognitive development. This integration produces graduates who are both intellectually competent and spiritually mature, capable of being salt and light in society. Contribution: This study contributes a practical emphasis on the necessity of integrating cognitive theory with Christ-centered spirituality in theological colleges to prevent intellectualism without moral integrity and to form graduates who reflect Jesus' character. Pendidikan di Sekolah Tinggi Teologi sering kali hanya mementingkan teori kognitif dan mengabaikan spiritualitas, sehingga mahasiswa cerdas secara intelektual tetapi kering secara rohani. Penelitian ini bertujuan untuk menyoroti pentingnya mengintegrasikan teori kognitif dan spiritualitas Kristen dalam pendidikan teologi agar mahasiswa tidak hanya menguasai pengetahuan tetapi juga memiliki karakter serupa Kristus. Penelitian ini menggunakan metode kajian pustaka kualitatif dengan menganalisis buku, jurnal, dan teks Alkitab yang berkaitan dengan teori belajar kognitif dan pembentukan rohani. Hasil penelitian menunjukkan bahwa tanpa spiritualitas yang berlandaskan Firman Tuhan dan teladan Yesus Kristus, kecerdasan kognitif yang tinggi dapat menyebabkan kesombongan, kegagalan moral, dan ketidakmampuan menjadi kesaksian hidup. Oleh karena itu, Sekolah Tinggi Teologi harus mengutamakan pembentukan spiritualitas—termasuk kerendahan hati, kasih, penguasaan diri, doa, dan ketaatan—bersamaan dengan pengembangan kognitif. Integrasi ini menghasilkan lulusan yang cakap secara intelektual sekaligus matang secara rohani, mampu menjadi garam dan terang di tengah masyarakat. Kontribusi: Penelitian ini memberikan kontribusi berupa penegasan praktis tentang perlunya mengintegrasikan teori kognitif dengan spiritualitas yang berpusat pada Kristus di Sekolah Tinggi Teologi, guna mencegah intelektualisme tanpa integritas moral dan membentuk lulusan yang mencerminkan karakter Yesus.